Aproximación inicial para el diagnóstico y manejo del paciente con tinnitus - Alvo V., Andrés; Nazar S., Rodolfo (Revista Hospital Clínico Universidad de Chile, 2010)
Tinnitus is a common disorder that affects 10-15% of the population and causes bothersome symptoms in up to 5%. Persistent tinnitus is frequently associated with hypoacusia. Clinically, it can be classified by its pulsatility and laterality, and also as being objective or subjective. An objective tinnitus can be identified by the examiner whereas subjective tinnitus cannot. A pulsatile tinnitus is usually associated with a vascular or inflammatory condition; non pulsatile tinnitus has broader diagnostic possibilities. The pathophysiology of subjective tinnitus is not completely understood, and there are several theories to explain it, which are probably complementary. In subjective, non pulsatile, bilateral tinnitus, the history, physical examination and audiological tests often suffice for establishing an accurate diagnosis. When these characteristics are not found, or if a vascular, tumoral or neurologic etiology is suspected, images must be considered. Although several treatments -both pharmacologic and non pharmacologic- are available for managing tinnitus, as of today there is no standard. High placebo effect rates, the need of trained specialists and difficulties in reproducing results explain this fact.